Gebiacantha sagamiensis, a new species of upogebiid shrimp (Crustacea: Decapoda: Gebiidea) from Sagami Bay, central Japan - Komai, Tomoyuki (Zootaxa, 2017)
A new species of the upogebiid shrimp genus Gebiacantha Ngoc-Ho, 1989, G. sagamiensis, is described and illustrated on the basis of a single male specimen collected from Sagami Bay, central Japan, at depths of 101–106 m. It appears closest to G. reunionensis Ngoc-Ho, 1989, known only from La Réunion, western Indian Ocean, but the different shape of the pleomere 6 and the better developed armature of the pereopod 1 carpus distinguish the new species from G. reunionensis. Comments on the taxonomic status of Gebiacantha and Paragebicula Sakai, 2006, and on the generic assignment of the new species, are given.